Cytotoxic effect of natural cuttlefish bone xenograft: an in vitro and in vivo study (Faculty of Medicine Universitas Indonesia, 2020)
BACKGROUND Commercialized synthetic bone grafts are commonly used to replace the bone defect. Cuttlefish bone is naturally available and widely studied, but the specific cytotoxicity test has not been conducted. This study aimed to evaluate the cytotoxicity of the xenograft compared to commercial grafts. METHODS We performed an in vitro test evaluating the viability of human mesenchymal stem cells (hMSCs) when cultured for 48 hours with the tested materials (cuttlefish bone graft and fabricated PerOssal®). The trypsinized mitochondrial activity of the viable hMSC was assayed based on colorimetry of the formazan color change. The tested material was considered nontoxic if >70% of the hMSCs were viable. The in vivo cytotoxic effect was evaluated by implanting the graft material in the femoral muscle of New Zealand (NZ) white rabbits. Nine rabbits were used in each test (cuttlefish bone, PerOssal®, and NaCl 0.9%). The systemic acute pyrogenic effect was evaluated based on 72 hours body weight changes and rectal temperature changes every 30 min in the first 3 hours and 72 hours post-implantation. RESULTSThe mean percentage of hMSC viability when cultured with cuttlefish bone graft and PerOssal® was comparable (93.47% and 105.37%, respectively, p = 0.240). The in vivo cytotoxicity on NZ rabbit was similar between all tested materials, as shown by the minor changes in body weight (<10% body weight, p = 0.391) and rectal temperature (<0.5°C, p = 0.127). CONCLUSIONS Cuttlefish bone xenograft and fabricated PerOssal® have a similar non-cytotoxic effects on hMSCs and non-pyrogenic systemic effects on rabbits.